Audio-visual-based history learning media materials about human life in the literary age - Insani, Marzius; Haenilah, Een Yayah; Hariri, Hasan; Sinaga, Risma Margaretha (Journal of Education and Learning (EduLearn), 2023)
This study aims to develop and test the feasibility of audio-visual-based learning media in history learning class X in senior high school. This study is a research and development (RD) type with the analyze, design, development, implementation, evaluation (ADDIE) model. The research involved 96 students of class X IPS or social science at State Senior High School 1 Bandar Lampung, Indonesia. The data collection techniques as well as the instruments employed questionnaires, observation, interviews, and documentation. Data analysis techniques employed qualitative and quantitative analysis. The results of the study show that: i) The development of audio-visual-based learning media on material about human life in Indonesia’s literacy period was made using the Adobe Photoshop application; and ii) The feasibility of the validation results of media experts, material experts, and learning experts (history teachers) successively with an average result of 4.73 (very good), 4.28 (very good), 4.50 (very good) and the results of the assessment students at 4.37 (very good). Then, the audio-visual-based learning media is declared feasible to use. This audio-visual-based historical learning media has its charm in being able to encourage students to become higher in learning history.